Making modern mothers : ethics and family planning in urban Greece - Paxson, Heather, 1968- (University of California Press, 2004)
Heather Paxson addresses the ambivalent perceptions of motherhood in Athens, as traditional views on femininity and childbearing are challenged by consumerism and imported biomedical family planning methods.